Self-reported depression and its associated factors among male inpatients admitted for substance use disorders in Saudi Arabia. (October 2015) - Alzahrani, Hatim; Barton, Peter; Brijnath, Bianca
Abstract Background: The association between depression and substance abuse is well established. However, uncertainties exist about the prevalence and comorbidity of substance use disorders and depression in Saudi Arabia. Methods: Data were collected from December 2012 to March 2013 from 165 male inpatients admitted for substance use disorders to a public health hospital in Jeddah. Participants completed a self-administered questionnaire. Depression was assessed using the Arabic version of the Beck Depression Inventory (BDI). Results: High BDI scores were reported by 95.2% of participants with more than two-thirds scoring severe (37%) or very severe (33.9%). Multivariate logistic regression indicated that those who had abused substances for more than 10 years were double the risk for depression compared to participants who had abused substances for less than 5 years (AOR = 2.16; 95% CI: 1.09–9.11). Those abusing substances for a duration of 5–10 years were likely to have a threefold risk for depression relative to participants who had a substance abuse history of less than 5 years (AOR = 3.08; 95% CI: 1.23–43.6). Conclusion: There is high prevalence of depression among substance users in Saudi Arabia. Prevalence and comorbidity is significantly associated with duration of substance abuse. Such findings have implications for treatment and service development as patients with these co-morbidities will require complex management.